Nature perfected the story of the garden ([S.l.] Public Media Video, 1995)
An enlightening documentary devoted to the art of gardening through out history.
Program one. Paradise on earth.-program, two. Ancient spirits : China and Japan.
VHS format.
Series written and narrated by William Howard Adams.
Keywords: Gardens -- History; Gardening -- History; Gardens -- Design -- History